Reconciliation The Antinomy of the Principle of Formal Legality and Living Law in Reformulation of National Criminal Law - Gede Yudi Sutrisna; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Dinasti Research, 2026)
The enactment of Law Number 1 of 2023 concerning the National Criminal Code (KUHP) brings a paradigm shift through the recognition of living law in Article 2, triggering an antinomy with the principle of formal legality in Article 1. This study aims to analyze the potential judicial conflict between customary law and formal legal certainty and its impact on the judicial system in Indonesia. The research method used is doctrinal legal research with a statutory and conceptual approach. The results indicate that the existence of the legality principle in the National Criminal Code is no longer absolute as it promotes the idea of balance between formal and material criteria. The prohibition of analogy in Article 1, Paragraph (2) specifically applies only to written law and does not hinder the application of living law to fill legal vacuums. Although aimed at achieving substantive justice, its implementation risks creating criminal disparities. Therefore, standardization through Local Regulations aligned with Pancasila values and sentencing guidelines for judges is required to bridge the gap between legal certainty and social justice.